Design of an info-electronic health system integrated to a notification application for dental clinics (Research, Society and Development, 2021)
A large part of the activity of health professionals consists of processing information that is, obtaining and recording clinical cases, information about the patient, either for legal reasons or as an initial and final comparison of the treatment proposed to the patient. Taking this reality into account, in which all these activities demand a lot of time and a specific structure, this article aims to describe an information network system and an application for mobile devices, with elements specific to this new technology, applicable both to healthcare professionals like to patients, features such as: accessibility, mobility and continuous ability to transfer data in real time. The prototype was built in a structured way, from a pilot project previously tested for the assertive choice of content development, choice of creation software, formatting, layout and indexing in app stores. After the prototype of the application was successfully tested, the following steps were allowed to pass, including testing by professionals and patients. The developed application proved to be a tool to aid diagnosis based on evidence and scientific literature to complement and guide the dental surgeon about the prevention, diagnosis and treatment of various oral pathologies, in addition to advising patients about care and their agenda. Thus, after finalized, the application can be indexed in the application stores (App Store and Google Play), with a cost for downloading, in addition to being necessary to register for use.